N-methyl-D-aspartate receptor hypofunction as a potential contributor to the progression and manifestation of many neurological disorders - Bin Dong; Yang Yue; Han Dong; Yuehui Wang (Frontiers in Molecular Neuroscience, 2023)
N-methyl-D-aspartate receptors (NMDA) are glutamate-gated ion channels critical for synaptic transmission and plasticity. A slight variation of NMDAR expression and function can result in devastating consequences, and both hyperactivation and hypoactivation of NMDARs are detrimental to neural function. Compared to NMDAR hyperfunction, NMDAR hypofunction is widely implicated in many neurological disorders, such as intellectual disability, autism, schizophrenia, and age-related cognitive decline. Additionally, NMDAR hypofunction is associated with the progression and manifestation of these diseases. Here, we review the underlying mechanisms of NMDAR hypofunction in the progression of these neurological disorders and highlight that targeting NMDAR hypofunction is a promising therapeutic intervention in some neurological disorders.